STUDI KASUS ANALISIS ASUHAN KEPERAWATAN PASIEN HIPERTENSI PADA MASALAH KEPERAWATAN NYERI AKUT DENGAN KOMBINASI PEMBERIAN BACK MASSAGE DAN TERAPI AKUPRESUR - Astanti, Tisna; Prihandani, IGAA Sherlyna; Yunita Sari, NLP Dian (Forind Press, 2025)
Headache is the most common complaint reported by hypertensive patients and is very disturbing in carrying out daily activities. Headache is caused due to an increase in blood pressure resulting in a decrease in oxygen to the brain which results in anaerobic metabolism and produces lactic acid and ultimately stimulates pain stimulation. Pain management is done to handle pain so that patients feel safe and comfortable, which can be done through pharmacological and non-pharmacological interventions such as autogenic relaxation, acupressure, back massage, foot massage, warm compresses and slow deep breathing. The purpose of writing this scientific paper is to know the analysis of nursing care hypertensive patients on pain nursing problems with a combination of giving back masage and acupressure therapy. The method in writing this scientific paper is a case study involving three patients hypertension with the provision of combined interventions of back massage therapy and acupressure. Data collection techniques used are interviews, observations, physical examinations, and documentation studies. The nursing problem found was pain associated with clinical manifestations of hypertension. The main intervention is pain management by providing a combination of back massage therapy and acupressure which is done once a day for 30 minutes and repeated for two days. The combination of back massage therapy and acupressure is effective in reducing complaints of headache pain that is experienced by the third.